2009
DOI: 10.4314/thrb.v11i2.45212
|View full text |Cite
|
Sign up to set email alerts
|

Low sensitivity but high specificity of ParaHIT-f in diagnosing malaria among children attending outpatient department in Butimba District Hospital, Mwanza, Tanzania

Abstract: Abstract:Malaria is the leading cause of mortality among under-fives in the sub-Saharan Africa. The gold standard method for the diagnosis of malaria is by the use of microscopy which is time consuming and requires skilled technicians. Recently the cost effective antigen based rapid diagnostic tests (RDTs) such as ParaHITf have been introduced in various places for the diagnosis of malaria. The choice of these RDTs to use in a certain country and specific geographical locations is critical to malaria diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
(11 reference statements)
3
10
2
Order By: Relevance
“…A similarly low sensitivity of the same test (9.6%) has been recorded in the Philippines, and a sensitivity of 29.8% to P. falciparum was reported from a holoendemic area of Tanzania in previous studies [10,17]. The observed results were inconsistent with those from similar studies in India and Tanzania, which have reported high sensitivity of the test raging from 70% -97% in different epidemiological settings [9,10,18,19].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…A similarly low sensitivity of the same test (9.6%) has been recorded in the Philippines, and a sensitivity of 29.8% to P. falciparum was reported from a holoendemic area of Tanzania in previous studies [10,17]. The observed results were inconsistent with those from similar studies in India and Tanzania, which have reported high sensitivity of the test raging from 70% -97% in different epidemiological settings [9,10,18,19].…”
Section: Discussionmentioning
confidence: 76%
“…For example, several studies from India and Tanzania have shown a high sensitivity and specificity of the ParaHIT-f rapid diagnostic test for diagnosis of Plasmodium falciparum malaria [9,12]. However, we have previously shown that, in a rural Tanzanian setting, sensitivity was low [10]. Thus monitoring the performance of ParaHIT-f, which is the most commonly used and inexpensive test available for malaria diagnosis in Tanzanian markets, remains important for accurate diagnosis and timely treatment of the disease.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the holoendemic areas of north-western Tanzania, the sensitivity and specificity of ParaHIT-f was 29.8%. There was a strong association between parasitaemia of ≥ 1000 parasites/μL and being positive for ParaHIT-f diagnostic test [16]. When the same test was subjected to an area characterized by low malaria transmission, the sensitivity was 10.7% [15].…”
Section: Introductionmentioning
confidence: 95%
“…In Tanzania, ParaHIT-f, ParaCheck-Pf and SD Bioline are currently been used for malaria diagnosis (National Malaria Control Programme personal Communication). In fact, SD Bioline has been recommended by the National Malaria Control Programme for use in all public health facilities [11][12][13][14][15]. The use of malaria RDTs have resulted into the decrease of misdiagnosis and use of ACTs among febrile patients in malaria endemic areas [7,12].…”
Section: Introductionmentioning
confidence: 99%